The Transformation of Islamic Economics in The Digital Era: An Analysis of Islamic Fintech and Financial Inclusion in Indonesia - Sarpini, Sarpini (Postgraduate, State Islamic University Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
The rapid expansion of Indonesia’s digital economy has transformed Islamic financial services through the emergence of sharia-compliant financial technologies, including Islamic peer-to-peer lending, equity crowdfunding, e-wallets, and digital zakat platforms. This study aims to examine the role of Islamic fintech in enhancing financial inclusion in Indonesia and to evaluate its implications for Islamic economic development within the framework of maqasid al-shariah. Employing a qualitative descriptive method based on recent academic literature, regulatory documents, and statistical reports (2020-2024), the findings indicate that Islamic fintech significantly contributes to expanding financial access, particularly among micro, small, and medium enterprises (MSMEs), women-led businesses, and rural communities previously underserved by conventional banking. However, the sector still faces major challenges, including fragmented regulations, low Islamic financial literacy, cybersecurity concerns, and limited institutional capacity in digital risk management. The novelty of this study lies in its integrated analysis of Islamic fintech from both a financial inclusion and Islamic legal-ethical perspective, emphasizing how value-based finance can complement digital innovation in Indonesia’s financial ecosystem. The study concludes that strengthening digital literacy, sharia compliance, data protection systems, and ecosystem collaboration between regulators, Islamic financial institutions, and technology providers is crucial for realizing inclusive Islamic digital finance in accordance with the objectives of maqasid al-shariah.